Reflections of an economic policy maker : speeches and congressional statements, 1969-1978 - Burns, Arthur F. (Washington : American Enterprise Institute for Public Policy Research, 1978)
The object of this study is divided into five parts. Part one discusses free enterprise and economic growth. Part two- inflation and unemployment. Part three- fiscal responsibility. Part four- sound money and banking, Part five- international finance.
Includes bibliographical footnotes and index.
ne 21/06/2018
Loans
Keywords: Inflation (Finance).; Unemployment; Free enterprise; Fiscal policy; United States